The prognostic impact of previously infectious complications on allogeneic hematopoietic stem cell transplantation for patients with severe aplastic anemia: A single-center, retrospective study - Zhang, Yuanfeng; Chen, Xin; Yang, Donglin; Pang, Aiming; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; He, Yi; Wei, Jialin; Jiang, Erlie; Han, Mingzhe; Feng, Sizhou (Frontiers in Immunology, 2022)
Whether infections before transplantation impair the survival of patients with severe aplastic anemia (SAA) remains unclear. The aim of this retrospective cohort analysis was to compare survival between patients with SAA who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) with infection (n=66) and patients without infection (n=189) from one medical center. There were no differences in baseline characteristics, except that more patients in the infection group were diagnosed with VSAA (59.09% vs. 30.69%, P<0.001), and their grafts were more peripheral blood stem cells (89.39% vs. 76.72%, P=0.042). Besides, the percentage of patients with multi-drug resistant organisms colonization or infection in the infection group was larger (16.7% vs. 0.5%, P<0.001). The median days of engraftment were similar between the two groups; however, the 28-day engraftment rates of neutrophils and platelets were lower in the infection group. No differences were observed in terms of grades II-IV acute graft versus host disease (aGVHD) (P=0.418), grades III-IV aGVHD (P=0.075), mild to severe chronic GVHD (cGVHD) (P=0.899), and moderate to severe cGVHD (P=0.342). Patients in the infection group had more bloodstream infections before engraftment (28.8% vs. 15.3%, P=0.016), and the primary cause of death was infection instead of aGVHD in contrast to patients without infection (16.7% vs. 4.2%, P=0.002). Finally, the estimated overall survival (OS), failure-free survival (FFS), and GVHD-free, FFS at 5 years were 63% (95% CI, 51–78), 60% (95% CI, 47–74), and 55% (95% CI, 43–70) in patients with infection before transplantation versus 86% (95% CI, 81–92) (P<0.001), 82% (95% CI, 76–88) (P<0.001), and 75% (95% CI, 69–82) (P=0.003) in patients without infection before transplantation. Multivariate analysis identified haploidentical HSCT and pre-HSCT anti-infection response, defined as partial remission (PR) or stable disease (SD), as adverse factors of OS and FFS. In conclusion, our study demonstrated that patients with infection defined as PR or SD but not complete remission before allo-HSCT showed inferior survival compared to patients without infection. Therefore, more attention should be paid to prophylaxis and complete control of infectious complications before transplantation.